Hunting for witchetty grubs - James, Margaret; Williams, Marjorie ([Wooli, New South Wales] : Honey Ant Readers, 2018)
Ancient practices of tracking and hunting come to life in this exciting series of learn-to-read books. Reading Tracks stories are written for older readers.
Reading Tracks® Progressive Learn-to-read series of book titles was inspired by the need to cater for Indigenous teenagers in Australia who find English print literacy a challenge.
"Inspired by hunting experiences with Elders Marjorie Williams and Jennifer Inkamala."--Front cover.
Keywords: Cossidae -- Juvenile fiction; Edible caterpillars -- Juvenile fiction; Wild foods -- Australia, Central -- Juvenile fiction; Aboriginal Australians -- Food -- Australia, Central -- Juvenile fiction; Readers (Primary) -- Aboriginal Australians; English language -- Study and teaching (Primary); Australian